Self-Inflicted Intraoral Hematoma in a Cardiac Patient Receiving Oral Anticoagulant Therapy- A Case Report - Shantala Arunkumar; Preethi A. Poonja; Shyam Amur; Atul P. Sattur; Krishna N. Burde; Venkatesh S Anehosur (Journal of Krishna Institute of Medical Sciences University)
Intraoral hematoma secondary to systemic anticoagulant therapy is rare, but it is a potentially fatal condition requiring immediate medical management. Case report: Here we report a case of self-inflicted hematoma in the anterior maxillary gingival region in a 65year old female cardiac patient who was on systemic anticoagulant therapy with a poor periodontal condition, manifesting as a periodontal swelling for a period of one week. Oral anticoagulant therapy is considerably imperative to prevent thromboembolic complications in various medical conditions, in such patients there are chances for spontaneous bleeding or hematoma by means of minor trauma due to sharp teeth or dental prosthesis in the mouth leading to life threatening complications such as partial or complete airway blockage. Therefore,directives about possible bleeding complications secondary to anticoagulant drugs in the oral cavity and the importance of maintaining oral health hygiene are necessary for the patient.